Does Copyright Imitation Impact Purchase Behaviour in the Entertainment Industry: A PLS-SEM Analysis of Gen Z’s Brand Recognition in Africa? - Abdulsalam, Tajudeen Alaburo; Tajudeen, Rofiat Bolanle (African Journal of Stability and Development (AJSD), 2024)
The entertainment industry has experienced remarkable growth, driven by technological advancements and changing consumer preferences, with revenue soaring to $31.23 billion in 2023 and anticipated growth at a Compound Annual Growth Rate (CAGR) of 10.64% through 2027. However, the industry’s significant sustainability issue is the widespread practice of copyright imitation, with Africa’s accommodated 2.5 billion unauthorised image imitations daily representing 1.48% global imitation index, causing substantial damages, notably affecting Gen Z with estimated losses of €532.5 billion, with Egypt experiencing the highest incidence of cases in Africa. This research delves into how copyright infringement impacts brand recognition, as a construct of purchase behaviour, among Gen Z in the African entertainment industry. By relying on post-positivism paradigm and planned behaviour theory, the research used questionnaire and collected 352 responses (92% sample rate) from tech-savvy Gen Z respondents, derived using Borden sampling model. The PLS-SEM (Partial Least Squares Structural Equation Modelling) model reveals that copyright infringement substantially affects brand recognition, explaining 64.7% of the variance in consumer behaviour. Specifically, imitated corporate names, product ideas, and promotional tactics impact brand recognition by 11.1%, 9%, and 6.2% respectively, which refutes the initial assumption. Research recommendations include implementing stricter management protocols within the industry, fostering deeper community engagement, and differentiating products by using unique, high-quality materials. The study acknowledges potential biases in data collection due to unequal online access among Gen Z music enthusiasts in Africa, by possibly not fully reflecting the broader diversity of Gen Z behaviour across the continent in the world, considering the varying cultural, economic, and social dynamics that influence purchasing behaviours.